Electroless plating of rhenium-based alloys with nickel, cobalt and iron. (20th August 2015) - Duhin, Alla; Inberg, Alexandra; Eliaz, Noam; Gileadi, Eliezer
Abstract: This paper focuses on electroless deposition of different Re-Me alloys, where Me is Co, Fe or Ni. The possibility to form high-quality Re-Ni films by this process has been demonstrated recently. In the current research we study and compare the influence of the iron-group metals on process kinetics, alloy composition and surface morphology. Alloys of Re-Ni (78 at.%), Re-Co (65 at.%) and Re-Fe (55 at.%) were prepared. Open-circuit potential measurements, as well as a polarization studies, were performed to investigate the induced co-deposition of Re with Ni, Co and Fe. It was shown that for Re-Co and Re-Ni alloys this process is controlled by a mixed-control reaction rather than by mass transport. Good agreement between the calculated and experimentally determined film deposition rates was obtained. Of the three iron-group metals, Ni was found to have the highest catalytic activity for reduction of R e O 4 − and formation of the Re-Me alloys.